BCT497: Adhesive and Coating Technology / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2017)
This course exposed the students to the various types of adhesives, jointing and coating systems used in the composite industry. Usage of hardware in modern construction will also be discussed. The selection and assembly process, focusing on ways to enhance strength, aesthetic value, and functionality of bio-composite products will be discussed.